earning environment: is there an influence of school and classroom space on education? - Stadler-Altmann, Ulrike (Formazione & insegnamento, 2018)
An overview of educational research on the influence of the constructed environment on educational practice is starting this paper: At first, some aspects for the evaluation of learning environment are presented, followed by two sections about school space and classroom space to show the importance of school buildings and classroom settings for teaching and learning processes. A focus is set on the coherency of the constructed school environment and the resultant challenges that occur for teaching and learning. Finally, further research questions are developed in the perspective of educational science and architectural psychology.